2023
DOI: 10.2169/internalmedicine.0076-22
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Granulomatous-lymphocytic Interstitial Lung Disease in a Patient with CTLA-4 Deficiency

Abstract: Common variable immunodeficiency (CVID) causes granulomatous-lymphocytic interstitial lung disease (GLILD) and has a poor prognosis. We herein report a case of GLILD in a 49-year-old woman with CTLA-4 deficiency-associated CVID. The patient presented with dyspnea that had worsened over the past two years. A laboratory examination revealed hypoglobulinemia and pancytopenia. Chest computed tomography showed diffuse infiltrative and granular shadows in the bilateral interstitium. A flow cytometric analysis of blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Flow-cytometry analysis including differential cell count was reported in 15 studies verifying significant lymphocytosis in 96/125 (78%) of patients ( 15 17 , 22 , 24 , 26 , 35 , 42 , 44 , 57 59 , 64 , 65 , 69 ). In addition, where lymphocyte phenotyping was performed this showed a larger proportion of B cells, predominantly CD21low B cells ( 57 , 65 ).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Flow-cytometry analysis including differential cell count was reported in 15 studies verifying significant lymphocytosis in 96/125 (78%) of patients ( 15 17 , 22 , 24 , 26 , 35 , 42 , 44 , 57 59 , 64 , 65 , 69 ). In addition, where lymphocyte phenotyping was performed this showed a larger proportion of B cells, predominantly CD21low B cells ( 57 , 65 ).…”
Section: Resultsmentioning
confidence: 97%
“…Pulmonary function tests (PFT) as assessment tools were reported in 40 studies ( 5 , 13 , 15 18 , 20 24 , 27 , 28 , 30 36 , 38 45 , 49 , 52 54 , 56 , 57 , 59 , 60 , 62 64 , 69 ), and included spirometry, measurement of diffusion capacity and assessment of static lung volumes (i.e., total lung capacity (TLC), and residual volume (RV)). Two studies reported PFT abnormalities as potential diagnostic criteria for CVID-ILD in addition to CT ( 64 , 65 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations